PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT. BFI FINANCE CABANG AMBON - Darto Rahayaan; Ambarwati Soetiksno; Roy Wattimena (P3M Politeknik Negeri Ambon, 2024)
Quality of service is one of the keys that must be owned by entrepreneurs, both those who are just starting a business or those who have been in the business world for years. That is, the quality of service is the level of service related to meeting the expectations and needs of consumers. That is, a service can be called quality if it meets most of the expectations of consumers. Service quality from PT. BFI Finance Ambon Branch has not been carried out optimally so that it has not been able to provide satisfaction to consumers. This study aims to determine the effect of service quality on consumer satisfaction at PT. BFI Finance Ambon Branch, the respondents involved in this study were 78 respondents, the sampling technique in this study used probability sampling. Data was collected using a survey method by distributing questionnaires to consumers. The data analysis used to test the hypothesis in this study is a simple linear regression analysis using SPSS 21.0 software. From the results of the hypothesis research, it produces a tcount value of 15,298 > 1,664 or at a significant value of 0,000 <0.05. The results of this study indicate that service quality has a positive effect on customer satisfaction at PT. BFI Finance Ambon Branch. Keywords: Service Quality, Consumer Satisfaction.